Edaphic and climatic factors influence on the distribution of soil transmitted helminths in Kogi East, Nigeria - Clement Ameh Yaro (Nature Portfolio, 2021)
Abstract The need for a reliable risk map in the control of soil-transmitted helminths (STHs) in Kogi East, North Central Nigeria is very important. This study was carried out to determine the effect of environmental risk factors on geospatial distribution of STHs. Epidemiological data were obtained from a district-wide survey conducted in 2018 in Kogi East. Edaphic and climatic factors were downloaded as spatial layers from international recognised health data resources centres. A total of 24 environmental factors were used in determining the risk map of STHs using MaxEnt tool. The predicted high-risk areas of A. lumbricoides, hookworms and S. stercoralis were the central part of Kogi East covering parts of Dekina, Ofu, Igalamela-Odolu, Olamaboro and Omala LGAs with probability of 0.8 to 1.00. Among the factors investigated; Temperature [mean diurnal temperature range (BIO2), temperature annual range (BIO7) and maximum temperature of the warmest month (BIO5)], precipitation [precipitation of the wettest quarter (BIO16)], and soil clay contents were the five factors that exerted most significant influence on the geospatial distribution of STHs in Kogi East, Nigeria. Public health control programmes on STHs should target high-risk areas by including them in mass drug administration, health education as well as provision of water, sanitation and hygiene infrastructures.